Adaptive reuse for sustainable urban development: vertical farming in former department stores. German case study - Bonekämper, Hanna (Frontiers in Built Environment, 2025)
Since digitalization has changed people’s shopping behavior, department stores have partly become obsolete. Concepts for adaptive reuse can help avoid future vacancies or counteract existing ones. However, developing viable concepts for reuse is challenging due to the layout of department stores, particularly regarding building depth, which limits natural light penetration throughout the structure. While vertical farming as a technology is not new, its integration into former department stores is. The unique contribution of this work lies in offering new perspectives on repurposing the growing number of vacant retail spaces. Through an architectural case study, this research explores how vertical farming could be implemented in such buildings. Using a department store in Wuppertal, Germany, as an example, the proposed solution is tailored to the site’s structural conditions. Methods from the field of architecture were applied, including a site analysis followed by an iterative design process that progressed from conceptual planning to detailed development. The results include floor plans, elevations, sections, and visualizations. The proposed design indicates that these buildings are well-suited for vertical farming, offering significant added value to the city. This contribution provides an interdisciplinary concept that uncovers further research questions.